Wide-awake local anaesthesia no tourniquet (WALANT) vs regional or general anaesthesia for flexor tendon repair in adults: protocol for a systematic review and meta-analysis - Nolan, Grant S. (Syst Rev, 2020)
BACKGROUND: Flexor tendon injuries most commonly occur following a penetrating injury to the hand or wrist. These are challenging injuries and the standard treatment is surgical repair under general or regional anaesthesia. ‘Wide-awake’ surgery is an emerging technique in hand surgery where a conscious patient is operated on under local anaesthetic. The vasoconstrictive effect of adrenaline (epinephrine) creates a ‘bloodless’ operating field and a tourniquet is not required. The potential advantages include intra-operative testing of the repair; removal of the risks of general anaesthesia; reduced costs; no aerosol generation from intubation therefore reduced risk of COVID-19 spread to healthcare professionals. The aim of this study will be to systematically evaluate the evidence to determine if wide-awake surgery is superior to general/regional anaesthetic in adults who undergo flexor tendon repair. METHODS: We designed and registered a study protocol for a systematic review and meta-analysis of comparative and non-comparative studies. The primary outcome will be functional active range of motion. Secondary outcomes will be complications, resource use (operative time) and patient-reported outcome measures. A comprehensive literature search will be conducted (from 1946 to present) in MEDLINE, EMBASE, CINAHL, and Cochrane Library. Grey literature will be identified through Open Grey, dissertation databases and clinical trials registers. All studies on wide-awake surgery for flexor tendon repair will be included. The comparator will be general or regional anaesthesia. No limitations will be imposed on peer review status or language of publication. Two investigators will independently screen all citations, full-text articles and abstract data. Potential conflicts will be resolved through discussion or referral to a third author when necessary. The study methodological quality (or bias) will be appraised using an appropriate tool. If feasible, we will conduct a random effects meta-analysis. DISCUSSION: This systematic review will summarise the best available evidence and definitively establish if function, complications, cost, or patient-reported outcomes are improved when flexor tendons are repaired using wide-awake technique. It will determine if this novel approach is superior to general or regional anaesthesia. This knowledge will help guide hand surgeons by continuing to improve outcomes from flexor tendon injuries. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42020182196 SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13643-020-01532-1.